2014
DOI: 10.3892/mmr.2014.2057
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of epigenomic, genomic and genetic alterations in the development of endometriosis (Review)

Abstract: Endometriosis is a complex disease influenced by genetic, epigenetic and environmental factors. The aim of the present study was to describe genomic instability, genetic polymorphisms and their haplotype, epigenetic alterations associated with predisposition to endometriosis, and the key factors associated with endometriosis-related ovarian neoplasms. Focus has been given on the developing paradigm that epigenetic alterations or genetic mutations in endometriosis may start in utero or in adolescent and young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 240 publications
(282 reference statements)
0
43
0
2
Order By: Relevance
“…9,10 It has been suggested that genetic, immunological, or environmental factors might be involved in this process. [10][11][12] Moreover, considering the malignant and immunological processes of the disease, the concept of a possible causal role of infectious agents has developed recently. 13,14 It has been suggested that intrauterine infection could initiate the endometriosis process by activating proinflammatory pathways and innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It has been suggested that genetic, immunological, or environmental factors might be involved in this process. [10][11][12] Moreover, considering the malignant and immunological processes of the disease, the concept of a possible causal role of infectious agents has developed recently. 13,14 It has been suggested that intrauterine infection could initiate the endometriosis process by activating proinflammatory pathways and innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps predictably, studies have also identified differential methylation/acetylation profiles between the eutopic endometrium and ectopic sites of tissue growth in women with endometriosis (for example, [132134]). Several functional studies linked altered decidualization capacity in women with endometriosis to abnormal epigenetic marks (ie, [135, 136]). For example, subjecting primary cultures of stromal cells, obtained from women with or without endometriosis, to a standard decidualization protocol, Bulun and colleagues identified a failure of decidualization-associated downregulation of DNMT3B hormones [137].…”
Section: Tcdd-mediated Epigenetic Eventsmentioning
confidence: 99%
“…Vielleicht führen die zyklisch wiederkehrenden Blutungen innerhalb der ovariellen Endometriome über eine Eisenüberladung und die Erhöhung von Sauerstoffradikalen zu genetischen Veränderungen [16,20,24]. So könnten durch das veränderte Mikromilieu im Epithel der ovariellen Endometriome somatische Mutationen akkumulieren, die über verschiedene Vorstufen ("atypische Endometriose") zur Entwicklung eines Ovarialkarzinoms führen.…”
Section: Molekulare Befundeunclassified